Dakwah Argumentatif Gus Muwafiq Pada Channel Youtube Santri Nusantara - Annisa Firdaus (AdZikra : Jurnal Komunikasi & Penyiaran Islam, 2023)
In general, language as a means of public communication is usually used by a certain group of people who are included in the language community. Language community are those who feel they have and use the same language. Community members have different backgrounds and social statuses. For example, there are differences in work, education, and so on. As a result of these differences there are language variations. This study aims to describe the forms of 1) idiolect variations, 2) dialect variations, 3) register variations, and 4) code switching variations carried out by K.H. Ahmad Muwafid. In today's digital era, humans are able to think quickly and instantly, modern humans now rely on the internet to fulfill their curiosity. Likewise, to hone knowledge that is broad and unlimited, now there is and can be accessed 24 hours on the internet, one of which is Youtube. Youtube is a website that provides various kinds of videos ranging from video clips to movies, as well as videos made by YouTube users themselves. On YouTube, many people express their ideas and opinions on various things, ranging from discussing the same things to discussing all existing things, both fiction and non-fiction. This is the same as what was conveyed by Ahmad Muwafiq or better known as Gus Muwafiq in one of his studies via the Gus Muwafiq Official YouTube channel. There, Gus Muwaffiq gave an in-depth study of the history of the arrival of Islam in the archipelago, with a number of things and customs that are still widely practiced by Muslims, of course, in a language that is also easy to understand.